Paediatric patient and family-centred care: ethical and legal issues - Zlotnik Shaul, Randi (International Library of Ethics, Law, and the New Medicine, 2014)
This book provides the reader with a theoretical and practical understanding of two health care delivery models: the patient/child centred care and family-centred care. Both are fundamental to caring for children in healthcare organizations. The authors address their application in a variety of paediatric healthcare contexts, as well as the ethical and legal issues they raise. Each model is increasingly pursued as a vehicle for guiding the delivery of health care in the best interests of children. Such models of health care delivery shape health care policies, programs, facility design, resource allocation decisions and day-to-day interactions among patients, families, physicians and other health care professionals. To maximize the health and ethical benefits these models offer, there must be shared understanding of what the models entail, as well as the ethical and legal synergies and tensions they can create. This book is a valuable resource for paediatricians, nurses, trainees, graduate students, practitioners of ethics and health policy.